Personality Trait Based Intervention for Workplace Accident Prevention - Yassierli, Yassierli; Nurhayati, Nurhayati; Anatasia, Marisa; Bahri, Shamsul (UI Scholars Hub, 2017)
Previous research has suggested that some traits may be useful as the predictors of risk behaviours behaviors. Therefore, personality traits seem to play a role in accident involvement. The purpose of this study is was to explore the relationship between the personality traits based on the Big Five Inventory (BFI) and worker accident experiences in order to elaborate personality traits based intervention for workplace accident prevention. A cross cross-sectional study was conducted among 173 workers in a cement company using a set of questionnaires consisting of respondents’ characteristics, BFI, and self-reported accident experience. The correlations were computed using Goodman Kruskal’s Gamma. A negative correlation between Extraversion dimension and accident experience was found to be approaching significant (G=- 0.273, p = 0.061). Workers with lower Extraversion dimensions, based on BFI, are recommended to have priority needs be prioritized for training or to be assigned to less hazardous workplaces.